Atomic Heterointerface Boosts the Catalytic Activity toward Oxygen Reduction/Evolution Reaction. Issue 45 (15th October 2021) - Lu, Xueyi; Yang, Yang; Yin, Yin; Wang, Ziling; Sutrisno, Linawati; Yan, Chenglin; Schmidt, Oliver G.
Abstract: Interface engineering is an efficient strategy to enhance the electrocatalytic activity of hybrid materials by taking advantage of the synergistic effect of double or even multiple active sites. Here, the rational design of a Pd/NiO atomic interface with well patterned Pd arrays imbedded into NiO thin films are reported to boost the catalytic activity toward the oxygen reduction/evolution reaction. Theoretical analysis elucidates that the Pd (111)/NiO (111) interface with minimized lattice mismatch effectively adsorbs intermediates (OH *, LiO2 *, Li2 O2 *, and Li2 O * ) and induces the growth/decomposition of electrochemical reaction products, which greatly lowers the Gibbs energy barrier of crucial steps and boosts the reaction kinetics. As expected, such hybrid thin films exhibit high catalytic activity for both the oxygen reduction reaction and oxygen evolution reaction, with performance comparable to the benchmarked Pt/C and RuO2 catalysts. Moreover, favorable performance is also achieved in both aqueous Zn–air batteries and aprotic Li–air batteries with an overpotential of only 0.69 and 0.50 V, respectively. This work suggests the great potential of such particularly morphological hybrid thin films in the development of high‐performance catalysts for energy storage and conversion. Abstract : Hybrid cathode catalysts consisting of Pd arrays decorated NiO thin films with atomic heterointerface are synthesized as Janus catalysts for the oxygen reduction/evolution reaction. Well patterned Pd arrays are imbedded into NiO thin films to improve the conductivity, stability and intermediates adsorption. Such bifunctional catalysts exhibit outstanding performance in both aqueous and aprotic metal‐air batteries with lowered overvoltages, extended cycle life, and excellent rate capability.